A negative electrode active material, a preparation method thereof, a negative electrode sheet, and a lithium ion battery
Patent Information
- Application Number
- CN202511943372.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-22
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2045-12-22
AI Technical Summary
[0005]本发明的主要目的是提出一种负极活性材料及其制备方法、负极片、锂离子电池,旨在解决现有技术中人造石墨负极材料的倍率性能较差的问题
[0016] In the technical solution of this invention, lithium doped in porous graphite can enhance the lithium-ion migration rate during charge and discharge, thereby improving the rate performance of the material. The lithium phosphate in the shell material has good solvation ability and good compatibility with the electrolyte solvent, thus enhancing the lithium-ion diffusion rate at the interface, improving the rate performance and low-temperature performance of the material, reducing surface defects in the core material, and improving the initial efficiency. The core lithium and shell lithium phosphate in the material of this invention can synergistically enhance the lithium-ion migration rate of the material, thereby synergistically improving the rate performance and cycle stability of the material, especially improving the capacity retention at low temperatures.
Smart Images

Figure CN121726374B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery material preparation technology, and in particular to a negative electrode active material and its preparation method, a negative electrode sheet, and a lithium-ion battery. Background Technology
[0002] Artificial graphite is a fast-charging anode material for lithium-ion batteries, but its rate performance is poor. This is because its highly ordered layered structure results in a long lithium-ion diffusion path, small interlayer spacing, low surface reactivity, and a high susceptibility to lithium plating during fast charging.
[0003] Coating the surface of artificial graphite with soft or hard carbon can provide non-oriented insertion channels for lithium ions, shortening the lithium ion diffusion path and thus improving the rate performance of the material at room temperature and low temperature. However, soft and hard carbon have a large specific surface area, which consumes a lot of lithium ions during the first charge and discharge to form a solid electrolyte interphase (SEI) film. Moreover, the SEI film is unstable at high temperatures, repeatedly breaking and regenerating, consuming lithium ions, resulting in poor high-temperature cycling and high-temperature storage performance.
[0004] Currently, coating the surface of artificial graphite with inorganic lithium salts guides the formation of a better artificial SEI film, reducing initial irreversible lithium loss and improving initial efficiency and rate performance. However, the improvement of the lithium-ion diffusion coefficient at the interface by inorganic lithium salts is limited, thus only providing a limited improvement in rate performance. High-rate materials (such as 4C and 6C charging) require extremely high ion flux, which a shell layer with a low diffusion coefficient cannot meet, leading to increased polarization and a higher risk of lithium plating. Furthermore, at low temperatures, the ionic conductivity of inorganic lithium salts decreases significantly with temperature, resulting in poor low-temperature fast charging performance. Summary of the Invention
[0005] The main objective of this invention is to propose a negative electrode active material and its preparation method, a negative electrode sheet, and a lithium-ion battery, aiming to solve the problem of poor rate performance of artificial graphite negative electrode materials in the prior art.
[0006] To achieve the above objectives, the present invention proposes a negative electrode active material, wherein the negative electrode active material comprises a core material and a shell material that at least partially encapsulates the core material: The core material includes porous graphite and nitrogen, lithium, carbon and oxygen elements doped into the pores of the porous graphite. The shell material includes lithium phosphate.
[0007] In one embodiment, the porous graphite has an average pore size of 8-12 μm; and / or, The thickness of the shell material is 0.5μm-2μm; and / or, The mass ratio of the porous graphite, nitrogen, lithium, carbon, oxygen, and lithium phosphate is 84-95.5:0.5-2:0.5-2:2-5:0.5-2:1-5.
[0008] The present invention also provides a method for preparing a negative electrode active material, the method comprising the following steps: S1. Porous graphite, inorganic lithium salt compound, conductive agent and nitrogen-containing alkaline organic solvent are mixed and chemically deposited to obtain the first precursor material. S2. The first precursor material is carbonized to obtain the second precursor material; S3. An organic solvent containing lithium phosphate is used to form a lithium phosphate deposition layer on the surface of the second precursor material by atomization deposition, followed by vacuum drying to obtain the negative electrode active material.
[0009] In one embodiment, in step S1, the porous graphite is obtained through the following steps: S01. The coke raw material, metal, metal oxide and binder are mixed and pressed into blocks to obtain a mixture; the boiling point of the metal is less than the boiling point of the metal oxide. S02. Under an inert atmosphere, the mixture is graphitized to obtain the porous graphite.
[0010] In one embodiment, in step S01, the mass ratio of the coke raw material, the metal, the metal oxide, and the binder is 100:1-5:1-5:10-30; and / or, In step S01, the coking raw material includes at least one of petroleum coke, needle coke, and pitch coke; and / or, In step S01, the metal includes at least one of potassium, sodium, and zinc; and / or, In step S02, the metal oxide includes at least one of tin oxide, titanium dioxide, vanadium oxide, iron oxide, and manganese oxide; and / or, The binder includes at least one of petroleum asphalt, coal tar pitch, and styrene.
[0011] In one embodiment, step S02 includes: subjecting the mixture to a first heat treatment under an inert atmosphere to volatilize the metal and obtain a first intermediate; subjecting the first intermediate to a second heat treatment to volatilize the metal oxide and obtain a second intermediate; and subjecting the second intermediate to a graphitization treatment to obtain the porous graphite.
[0012] In one embodiment, the temperature of the first heat treatment is 700-900°C; and / or, The first heat treatment lasts for 2-6 hours; and / or, The temperature of the second heat treatment is 1100-1400℃; and / or, The second heat treatment lasts for 2-6 hours; and / or, The graphitization treatment is performed at a temperature of 2800-3200℃; and / or, The graphitization process takes 6-24 hours.
[0013] In one embodiment, in step S1, the inorganic lithium salt compound includes at least one of LiTi2(PO4)3, LiGe2(PO4)3, and LiZr2(PO4)3; and / or, In step S1, the conductive agent includes at least one of graphene, carbon nanotubes, and super carbon black; and / or, In step S1, the nitrogen-containing alkaline organic solvent includes at least one of dimethylacetamide, dimethylformamide, and phenylacetamide; and / or, In step S1, the mass ratio of the porous graphite, the inorganic lithium salt compound, the conductive agent, and the alkaline organic solvent is 100:5-10:1-5:500-1000; and / or, In step S1, the temperature of the chemical deposition treatment is 25-80℃; and / or, In step S1, the chemical deposition treatment takes 1-6 hours; and / or, In step S2, the carbonization treatment temperature is 800-1200℃; and / or, In step S2, the carbonization treatment time is 1-6 hours; and / or, In step S3, the concentration of lithium phosphate in the organic solvent containing lithium phosphate is 1-5 wt%; and / or, In step S3, the temperature of the atomization deposition method is 60-200℃; and / or, In step S3, the pressure of the atomization deposition method is 1-10 MPa; and / or, In step S3, the atomization deposition method takes 30-300 minutes; and / or, In step S3, the vacuum drying temperature is 80~90℃; and / or, In step S3, the vacuum drying time is 22-26 hours.
[0014] The present invention also provides a negative electrode sheet, the negative electrode sheet comprising the aforementioned negative electrode active material or the negative electrode active material prepared by the aforementioned method for preparing negative electrode active material.
[0015] The present invention also provides a lithium-ion battery, wherein the lithium-ion battery includes the aforementioned negative electrode.
[0016] In the technical solution of this invention, lithium doped in porous graphite can enhance the lithium-ion migration rate during charge and discharge, thereby improving the rate performance of the material. The lithium phosphate in the shell material has good solvation ability and good compatibility with the electrolyte solvent, thus enhancing the lithium-ion diffusion rate at the interface, improving the rate performance and low-temperature performance of the material, reducing surface defects in the core material, and improving the initial efficiency. The core lithium and shell lithium phosphate in the material of this invention can synergistically enhance the lithium-ion migration rate of the material, thereby synergistically improving the rate performance and cycle stability of the material, especially improving the capacity retention at low temperatures. Attached Figure Description
[0017] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on the structures shown in these drawings without creative effort.
[0018] Figure 1 The image shows a scanning electron microscope (SEM) image of the negative electrode active material prepared in Example 1 of this invention.
[0019] The realization of the objective, functional features and advantages of the present invention will be further explained in conjunction with the embodiments and with reference to the accompanying drawings. Detailed Implementation
[0020] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Where the manufacturers of reagents or instruments are not specified, they are all conventional products that can be purchased commercially. Furthermore, the meaning of "and / or" throughout the text includes three parallel solutions; for example, "A and / or B" includes solution A, or solution B, or a solution where both A and B are satisfied simultaneously. In addition, the technical solutions of the various embodiments can be combined with each other, but this must be based on the ability of those skilled in the art to implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such a combination of technical solutions does not exist and is not within the scope of protection claimed by the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0021] Artificial graphite is a fast-charging anode material for lithium-ion batteries, but its rate performance is poor. This is because its highly ordered layered structure results in a long lithium-ion diffusion path, small interlayer spacing, low surface reactivity, and a high susceptibility to lithium plating during fast charging.
[0022] Coating the surface of artificial graphite with soft or hard carbon can provide non-oriented insertion channels for lithium ions, shortening the lithium ion diffusion path and thus improving the rate performance of the material at room temperature and low temperature. However, soft and hard carbon have a large specific surface area, which consumes a lot of lithium ions during the first charge and discharge to form a solid electrolyte interphase (SEI) film. Moreover, the SEI film is unstable at high temperatures, repeatedly breaking and regenerating, consuming lithium ions, resulting in poor high-temperature cycling and high-temperature storage performance.
[0023] Currently, coating the surface of artificial graphite with inorganic lithium salts guides the formation of a better artificial SEI, reducing initial irreversible lithium loss and improving initial efficiency and rate performance. However, the improvement of the lithium-ion diffusion coefficient at the interface by inorganic lithium salts is limited, thus only providing a limited improvement in rate performance. High-rate materials (such as 4C and 6C charging) require extremely high ion flux, which a shell layer with a low diffusion coefficient cannot meet, leading to increased polarization and a higher risk of lithium plating. Furthermore, at low temperatures, the ionic conductivity of inorganic lithium salts decreases significantly with temperature, resulting in poor low-temperature fast charging performance.
[0024] In view of this, the present invention proposes a negative electrode active material, the negative electrode active material comprising a core material and a shell material at least partially covering the core material: the core material comprises porous graphite and nitrogen, lithium, carbon and oxygen elements doped in the pores of the porous graphite; the shell material comprises lithium phosphate.
[0025] In the technical solution of this invention, lithium doped in porous graphite can enhance the lithium-ion migration rate during charge and discharge, thereby improving the rate performance of the material. The lithium phosphate in the shell material has good solvation ability and good compatibility with the electrolyte solvent, thus enhancing the lithium-ion diffusion rate at the interface, improving the rate performance and low-temperature performance of the material, reducing surface defects in the core material, and improving the initial efficiency. The core lithium element and the shell lithium phosphate in the material of this invention can synergistically enhance the lithium-ion migration rate of the material, thereby synergistically improving the rate performance and cycle stability of the material, especially improving the capacity retention at low temperatures.
[0026] It should be noted that lithium phosphate has a strong solvation ability, and its phosphate ion (PO4) 4- Lithium ions (Li) can be modulated through electrostatic interactions. + The solvation structure of Li lowers the solvation energy barrier and promotes Li +The desolvation process improves the lithium-ion insertion / extraction rate.
[0027] In the negative electrode active material of this invention, lithium in porous graphite can enhance the diffusion rate of lithium ions in the core material, thereby improving the rate performance of the material. However, the improvement is relatively small because the lithium ion diffusion rate at the interface is low. Lithium phosphate in the shell material can enhance the lithium ion diffusion rate at the shell interface, thereby significantly improving the rate performance of the material, especially at low temperatures. The two methods synergistically improve the overall rate performance of the negative electrode active material. At the same time, the solvation capability of lithium phosphate in the shell material can reduce side reactions, reduce lithium ion loss, and improve storage performance.
[0028] It should be noted that the carbon element in the negative electrode active material of the present invention is amorphous carbon, which is formed by carbonization of the same substance as nitrogen. Therefore, it is actually nitrogen-doped amorphous carbon existing in the porous graphite voids.
[0029] In some embodiments, the average pore size of the porous graphite is 8-12 μm. An average pore size within this range ensures good structural strength stability of the pores and good material compaction density.
[0030] In some embodiments, the thickness of the shell material is 0.5 μm-2 μm. A thickness within this range ensures that the shell material effectively encapsulates the core material and that the shell material has a high lithium-ion diffusion rate.
[0031] In some embodiments, the mass ratio of the porous graphite, nitrogen, lithium, carbon, oxygen, and lithium phosphate is 84-95.5:0.5-2:0.5-2:2-5:0.5-2:1-5. This mass ratio can be 84:2:2:5:2:5, 95.5:0.5:0.5:2:0.5:1, or 91:1:1:3:1:3. A mass ratio within these ranges ensures good overall rate performance and initial efficiency of the material.
[0032] This invention also provides a method for preparing a negative electrode active material, the method comprising the following steps: S1, mixing porous graphite, an inorganic lithium salt compound, a conductive agent and a nitrogen-containing alkaline organic solvent, and performing chemical deposition treatment to obtain a first precursor material; S2, carbonizing the first precursor material to obtain a second precursor material; S3, forming a lithium phosphate deposition layer on the surface of the second precursor material using an organic solvent containing lithium phosphate via atomization deposition, and vacuum drying to obtain the negative electrode active material.
[0033] In the technical solution of this invention, in step S1, porous graphite, an inorganic lithium salt compound, a conductive agent, and a nitrogen-containing alkaline organic solvent are mixed and subjected to chemical deposition. During the chemical deposition process, lithium ions in the inorganic lithium salt compound and hydroxide ions in the nitrogen-containing alkaline organic solvent combine to form lithium hydroxide, which is then deposited in the pores of the porous graphite to obtain a first precursor material. The first precursor material is then carbonized, causing the deposited lithium hydroxide to decompose at the carbonization temperature to generate lithium oxide and water vapor. The evaporation of the water vapor leaves behind some microporous structures, resulting in porous lithium oxide, thus obtaining a second precursor material. A lithium phosphate deposition layer, i.e., a shell material, is then formed on the surface of the second precursor material to obtain the negative electrode active material. This negative electrode active material possesses all the aforementioned beneficial effects.
[0034] It should be noted that lithium oxide and conductive agents have good ionic and electronic conductivity, respectively, which can improve the electronic and ionic conductivity of the graphite core matrix and improve rate performance.
[0035] In some embodiments, in step S1, the porous graphite is obtained by the following steps: S01, mixing and pressing coke raw material, metal, metal oxide and binder to obtain a mixture; the boiling point of the metal is less than the boiling point of the metal oxide; S02, graphitizing the mixture under an inert atmosphere to obtain the porous graphite.
[0036] In the technical solution of this invention, in step S01, coke raw material, metal, metal oxide and binder are mixed and pressed into blocks. The binder can bind the dispersed metal and metal oxide together, playing a role in ensuring adhesion during dispersion, so that the metal and metal oxide are well dispersed in the coke raw material and can be bound together to obtain a mixture. In step S02, the mixture is subjected to graphitization treatment. On the one hand, the coke raw material and binder are converted into graphite. On the other hand, the boiling points of the metal and metal oxide are both lower than the graphitization treatment temperature. At the high temperature of graphitization, the metal and metal oxide volatilize and leave pores in their original positions. These pores, due to having the size of both metal and metal oxide, form nano- or even micro-pores, thereby obtaining porous graphite.
[0037] In some embodiments, in step S01, the mass ratio of the coke raw material, the metal, the metal oxide, and the binder is 100:1-5:1-5:10-30. This mass ratio can be 100:1:1:10, 100:3:3:20, or 100:5:5:30. A mass ratio within these ranges ensures good bonding between the metal and the metal oxide, resulting in a suitable and stable porous structure during subsequent graphitization, without reducing the material's structural strength and compaction density.
[0038] In some embodiments, in step S01, the coking raw material includes at least one of petroleum coke, needle coke, and pitch coke. That is, the coking raw material can be any one of petroleum coke, needle coke, and pitch coke, or two or three of them, all of which are within the scope of protection of this invention.
[0039] In some embodiments, the binder includes at least one of petroleum asphalt, coal tar pitch, and styrene. That is, the binder can be any one of petroleum asphalt, coal tar pitch, and styrene, or two or three of these, all within the scope of this invention. The above-mentioned binder can effectively bond coke raw materials, metals, and metal oxides.
[0040] In some embodiments, in step S01, the metal includes at least one of potassium, sodium, and zinc; and / or, the metal oxide includes at least one of tin oxide, titanium dioxide, vanadium oxide, iron oxide, and manganese oxide. That is, the metal may include any one of potassium, sodium, and zinc, or two or three of these, and the metal oxide may be any one of tin oxide, titanium dioxide, vanadium oxide, iron oxide, and manganese oxide, or two or more of these, all within the scope of this invention. Simultaneously selecting the above-mentioned metal and metal oxide ensures that the boiling point of the metal is lower than that of the metal oxide.
[0041] It is understandable that metals and metal oxides have different boiling points, and at the graphitization temperature, due to the high temperature, both will actually volatilize simultaneously. However, preferably, in some embodiments, step S02 includes: subjecting the mixture to a first heat treatment under an inert atmosphere to volatilize the metal, obtaining a first intermediate; subjecting the first intermediate to a second heat treatment to volatilize the metal oxide, obtaining a second intermediate; and subjecting the second intermediate to graphitization treatment to obtain the porous graphite.
[0042] In the technical solution of this invention, a first heat treatment is performed to remove moisture and light volatile components from the mixture, forming first-type pores. A second heat treatment is then performed to volatilize the metal, forming second-type pores. Finally, a graphitization treatment is performed to volatilize the metal oxide, forming third-type pores, simultaneously reducing porosity and increasing specific capacity, resulting in porous graphite. Specifically, moisture and light components in the mixture volatilize first to form pores. Further heating causes the lower-boiling-point metal to form pores, and continued heating enlarges the pores, allowing multiple small pores to connect and form larger pores. Simultaneously, the higher-boiling-point metal oxide volatilizes, leaving pores, forming a gradient pore structure. This gradient pore structure avoids the simultaneous volatilization of two substances, which would reduce the strength of the porous structure. This results in porous graphite with suitable nano- and micro-sized pores, good pore structure strength and compaction density, and a large specific surface area, ensuring the electrochemical performance of the battery prepared from the material. It should be noted that the binder also generates highly isotropic amorphous carbon, i.e., graphitic carbon, throughout the process. Metal oxides can also be used as negative electrode materials, exhibiting high specific capacity. Therefore, metal oxides can partially generate pores during the heating and volatilization process, leaving a small amount of unvolatilized metal oxides that also serve as part of the negative electrode material, resulting in minimal capacity loss. In the technical solution of this invention, the residual amount of metal oxides is typically ≤0.5%.
[0043] In some embodiments, the temperature of the first heat treatment is 700-900°C; and / or the time of the first heat treatment is 2-6 hours; and / or the temperature of the second heat treatment is 1100-1400°C; and / or the time of the second heat treatment is 2-6 hours; and / or the temperature of the graphitization treatment is 2800-3200°C; and / or the time of the graphitization treatment is 6-24 hours. That is, the temperature of the first heat treatment can be 700℃, 800℃ or 900℃, and the time of the first heat treatment can be 2h, 4h or 6h. The temperature of the second heat treatment can be 1100℃, 1200℃ or 1400℃, and the time of the second heat treatment can be 2h, 4h or 6h. The temperature of the graphitization treatment can be 2800℃, 3000℃ or 3200℃, and the time of the graphitization treatment can be 6h, 12h or 24h. By controlling the temperature and time of the first heat treatment, the second heat treatment and the graphitization treatment within the above range, it can be ensured that the metal and metal oxide volatilize in sequence, and finally form gradient pores. The material has good structural stability and rate performance.
[0044] In some embodiments, in step S1, the inorganic lithium salt compound includes at least one of LiTi2(PO4)3, LiGe2(PO4)3, and LiZr2(PO4)3. That is, the inorganic lithium salt compound can be any one of LiTi2(PO4)3, LiGe2(PO4)3, and LiZr2(PO4)3, or two or three of them, all within the scope of this invention. The above-mentioned inorganic lithium salt compounds all have high ionic conductivity, belonging to fast ion conductors, and can improve the lithium ion diffusion rate in the core of the negative electrode active material.
[0045] In some embodiments, in step S1, the conductive agent includes at least one of graphene, carbon nanotubes, and supercarbon black; and / or, the nitrogen-containing alkaline organic solvent includes at least one of dimethylacetamide, dimethylformamide, and phenylacetamide. That is, the conductive agent can be any one of graphene, carbon nanotubes, and supercarbon black, or two or three of these three substances; the nitrogen-containing alkaline organic solvent can be any one of dimethylacetamide, dimethylformamide, and phenylacetamide, or two or three of these three substances, all within the scope of this invention. The above-mentioned conductive agent has good electronic conductivity, which can improve the electronic conductivity of the material; the above-mentioned nitrogen-containing alkaline organic solvent can uniformly disperse the conductive agent and inorganic lithium salt compound, avoiding agglomeration, and can form a nitrogen-doped amorphous structure after carbonization. It is understood that the conductive agent can be added to the system in the form of a conductive agent solution, which can be formed by mixing the conductive agent with a solvent such as N-methylpyrrolidone, and its concentration is preferably 1-5 wt%.
[0046] In some embodiments, in step S1, the mass ratio of the porous graphite, the inorganic lithium salt compound, the conductive agent, and the alkaline organic solvent is 100:5-10:1-5:500-1000. This mass ratio can be 100:10:5:1000, 100:7:3:700, or 100:5:1:500; a mass ratio within the above range can ensure a good chemical deposition effect.
[0047] In some embodiments, in step S1, the temperature of the chemical deposition treatment is 25-80°C; and / or, in step S1, the time of the chemical deposition treatment is 1-6 hours. The temperature of the chemical deposition treatment can be 25°C, 60°C, or 80°C, and the time of the chemical deposition treatment can be 1 hour, 3 hours, or 6 hours. Controlling the temperature and time of the chemical deposition treatment within the above ranges can ensure uniform deposition of lithium hydroxide compound in the pores of porous graphite.
[0048] In some embodiments, in step S2, the carbonization temperature is 800-1200℃; and / or, in step S2, the carbonization time is 1-6 hours. The carbonization temperature can be 800℃, 1000℃, or 1200℃, and the carbonization time can be 1 hour, 3 hours, or 6 hours. Controlling the carbonization temperature and time within the above ranges ensures that the lithium hydroxide formed by chemical deposition undergoes thermal decomposition to form lithium oxide, and that the hydrogen and oxygen in the nitrogen-containing alkaline organic solvent undergo sufficient thermal decomposition and volatilization to form structurally stable amorphous carbon.
[0049] In some embodiments, in step S3, the concentration of lithium phosphate in the organic solvent containing lithium phosphate is 1-5 wt%; and / or, in step S3, the temperature of the atomization deposition method is 60-200°C; and / or, in step S3, the pressure of the atomization deposition method is 1-10 MPa; and / or, in step S3, the time of the atomization deposition method is 30-300 min. The concentration of lithium phosphate in the organic solvent can be 1 wt%, 3 wt%, or 5 wt%; the temperature of the atomization deposition method can be 60°C, 150°C, or 200°C; the pressure of the atomization deposition method can be 1 MPa, 6 MPa, or 10 MPa; and the time of the atomization deposition method can be 30 min, 200 min, or 300 min. Simultaneously controlling the concentration of lithium phosphate, the temperature, pressure, and time of the atomization deposition method within the above ranges ensures the formation of a relatively uniform and thick lithium phosphate layer on the surface of the core material.
[0050] In some embodiments, in step S3, the vacuum drying temperature is 80~90℃; and / or, in step S3, the vacuum drying time is 22~26h. Simultaneously controlling the vacuum drying temperature and time within the above range ensures sufficient evaporation of the organic solvent.
[0051] The present invention also provides a negative electrode sheet, wherein the negative electrode sheet comprises the aforementioned negative electrode active material or the negative electrode active material prepared by the aforementioned method for preparing the negative electrode active material. Therefore, it possesses all the beneficial effects of the aforementioned negative electrode active material or the aforementioned method for preparing the negative electrode active material, which will not be elaborated further here.
[0052] The present invention also provides a lithium-ion battery, which includes the aforementioned negative electrode. Therefore, it possesses all the beneficial effects of the aforementioned negative electrode, which will not be elaborated further here.
[0053] The technical solution of the present invention will be further described in detail below with reference to specific embodiments and accompanying drawings. It should be understood that the following embodiments are only used to explain the present invention and are not intended to limit the present invention.
[0054] Example 1 A negative electrode active material includes a core material and a shell material covering the core material. The core material includes porous graphite and nitrogen, lithium, carbon and oxygen elements doped into the pores of the porous graphite. The shell material includes lithium phosphate. The negative electrode active material is prepared through the following steps: Step S01: Weigh 100g of petroleum coke, 3g of metallic potassium, 3g of tin oxide and 20g of petroleum asphalt binder, mix them evenly and press them into blocks to obtain a mixture; Step S02: Under an inert argon atmosphere, the mixture is first heated to 800℃ for a first heat treatment for 4 hours, then heated to 1200℃ for a second heat treatment for 4 hours, and finally heated to 3000℃ for a graphitization treatment for 12 hours to obtain porous graphite. Step S1: Add 8g LiTi2(PO4)3 and 100g 3wt% graphene to 800g dimethylacetamide solvent and disperse evenly. Then add 100g porous graphite and perform chemical deposition at 50℃ for 3h. Filter and take the filter residue, which is the first precursor material. Step S2: Carbonize the obtained filter residue at 950℃ for 3 hours to obtain the second precursor material; Step S3: Add 5g of lithium phosphate to 200g of dimethyl carbonate solution to prepare a 3wt% mixed solution. Then, transfer the second precursor material to the atomization device as a substrate by atomization. Set the parameters as follows: temperature 100℃, pressure 5MPa. Atomize the mixed solution and deposit lithium phosphate on the surface of the second precursor material for 150min. Dry the resulting material under vacuum at 80℃ for 24h to obtain the negative electrode active material.
[0055] Example 2 A negative electrode active material includes a core material and a shell material covering the core material. The core material includes porous graphite and nitrogen, lithium, carbon and oxygen elements doped into the pores of the porous graphite. The shell material includes lithium phosphate. The negative electrode active material is prepared through the following steps: Step S01: Weigh 100g of needle coke, 1g of metallic sodium, 1g of titanium dioxide and 10g of coal tar pitch binder, mix them evenly and press them into blocks to obtain a mixture; Step S02: Under an inert argon atmosphere, the mixture is first heated to 700℃ for a first heat treatment for 6 hours, then heated to 1100℃ for a second heat treatment for 6 hours, and finally heated to 2800℃ for a graphitization treatment for 24 hours to obtain porous graphite. Step S1: Add 5g LiGe2(PO4)3 and 100g 1wt% carbon nanotube conductive agent to 500g dimethylformamide and disperse evenly. Then add 100g porous graphite and perform chemical deposition at 25℃ for 6h. Filter and take the filter residue, which is the first precursor material. Step S2: Carbonize the obtained filter residue at 800℃ for 6 hours to obtain the second precursor material; Step S3: Add 1g of lithium phosphate to 100g of dimethyl carbonate solution to prepare a 1wt% mixed solution. Then, transfer 100g of the second precursor material to the atomization device as a substrate by atomization. Atomize the mixed solution according to the following parameters: temperature 60℃, pressure 10MPa. Deposit lithium phosphate on the surface of the second precursor material for 30min. Dry the resulting material under vacuum at 80℃ for 24h to obtain the negative electrode active material.
[0056] Example 3 A negative electrode active material includes a core material and a shell material covering the core material. The core material includes porous graphite and nitrogen, lithium, carbon and oxygen elements doped into the pores of the porous graphite. The shell material includes lithium phosphate. The negative electrode active material is prepared through the following steps: Step S01: Weigh 100g of pitch coke, 5g of zinc metal, 5g of vanadium oxide and 30g of styrene binder, mix them evenly and press them into blocks to obtain a mixture; Step S02: Under an inert argon atmosphere, the mixture is first heated to 900℃ for a first heat treatment for 2 hours, then heated to 1400℃ for a second heat treatment for 2 hours, and finally heated to 3200℃ for a graphitization treatment for 6 hours to obtain porous graphite. Step S1: Add 10g LiZr2(PO4)3 and 100g 5wt% super carbon black conductive agent to 1000g phenylacetamide and disperse evenly. Then add 100g porous graphite and perform chemical deposition at 80℃ for 1h. Filter and take the filter residue, which is the first precursor material. Step S2: Carbonize the obtained filter residue at 1200℃ for 1 hour to obtain the second precursor material; Step S3: Add 5g of lithium phosphate to 100g of dimethyl carbonate solution to prepare a 5wt% mixed solution. Then, transfer the second precursor material to the atomization device as a substrate by atomization. Set the parameters as follows: temperature 200℃, pressure 1MPa. Atomize the mixture and deposit lithium phosphate on the surface of 100g of the second precursor material for 300min. Dry the resulting material under vacuum at 80℃ for 24h to obtain the negative electrode active material.
[0057] Example 4 The difference between Example 4 and Example 1 is that: In step S02, the mixture is heated to 3000℃ and graphitized for 12 hours under an inert argon atmosphere to obtain porous graphite.
[0058] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that: Step S1 is the same as in Example 1, except that LiTi2(PO4)3 is not added.
[0059] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that: In step S3, lithium phosphate is not added; that is, the second precursor material in step S2 is used as the negative electrode active material.
[0060] Performance testing The negative electrode active material prepared in Example 1 was observed by scanning electron microscopy, and the results are as follows: Figure 1 As shown.
[0061] Depend on Figure 1 It can be seen that the negative electrode active material prepared in Example 1 exhibits a secondary particle structure with a particle size between 8-12 μm.
[0062] The physicochemical properties of the negative electrode active materials prepared in Examples 1-4 and Comparative Examples 1-2 were tested using the following methods: The tap density and specific surface area of the negative electrode active materials in Examples 1-3 and Comparative Examples 1-2 were tested according to the test methods in standard GB / T-24533-2019 "Graphite Anode Materials for Lithium-ion Batteries". The OI value (Orientation Index) of the powder materials was tested by XRD, and the diffusion coefficient was tested by GITT (Galvanostatic Titration). The test results are shown in Table 1.
[0063] Table 1. Performance characterization of the negative electrode active materials prepared in Examples 1-4 and Comparative Examples 1-2
[0064] As shown in Table 1, the diffusion coefficient, tap density, and OI value of the negative electrode active materials prepared in Examples 1-4 are significantly better than those in Comparative Examples 1-2. Comparing Examples 1, 1, and 2, the lithium-ion diffusion coefficient (i.e., the diffusion coefficient in the table) of the examples is significantly improved, indicating that the lithium core doping and the lithium phosphate shell have a synergistic effect, which synergistically improves the lithium-ion diffusion rate of the material. Compared with Examples 1 and 4, by performing gradient heating to make the internal porous structure more uniform and avoid the formation of macroporous structures, the tap density and specific surface area of the material are improved while maintaining a good diffusion coefficient.
[0065] Button cell battery test: The negative electrode active materials of Examples 1-4 and Comparative Examples 1-2 were assembled into coin cells according to the following method: The negative electrode active materials prepared in Examples 1-4 and Comparative Examples 1-2 were used as negative electrodes and assembled into coin cells with lithium sheets, electrolytes, and separators in a glove box with argon and water contents both below 0.1 ppm. The separator was Celegard 2400; the electrolyte was a LiPF6 solution with a LiPF6 concentration of 1 mol / L, and the solvent was a mixed solution of ethylene carbonate (EC) and diethyl carbonate (DMC) in a 1:1 weight ratio.
[0066] The fabricated coin cells were tested using a blue-light tester. The test conditions were: 0.1C charge-discharge rate, voltage range of 0.05-2V, 3 cycles, followed by testing the discharge capacity at 1C. The 1C / 0.1C rate performance, cycle performance (25±3℃, 0.2C / 0.2C, 100 cycles), and low-temperature capacity retention (-20℃ capacity / 25℃ capacity) were calculated. The test results are shown in Table 2.
[0067] Table 2 Performance characterization of coin cells corresponding to Examples 1-4 and Comparative Examples 1-2
[0068] As shown in Table 2, the specific capacity, initial efficiency, rate capability, and cycle performance of the coin cells corresponding to Examples 1-4 are significantly better than those of Comparative Examples 1-2. This may be because the materials in these examples are doped with lithium, which increases the diffusion coefficient and reduces irreversible capacity loss, thereby improving the initial efficiency and rate performance. Simultaneously, coating the porous graphite surface with a fast-ion conductor and a conductive agent utilizes the high ionic conductivity of the fast-ion conductor and the high electronic conductivity of the conductive agent to reduce polarization and improve rate performance. Furthermore, lithium phosphate exhibits good compatibility with the electrolyte lithium hexafluorophosphate and possesses an excellent lithium-ion diffusion rate, improving rate performance and low-temperature performance.
[0069] Furthermore, compared to Example 4, Example 1 exhibits better electrochemical performance. This is because, in Example 1, the use of stepped heating allows the volatiles in the coke raw material to slowly evaporate, resulting in a more stable structure. Simultaneously, the metals and metal oxides also undergo stepped heating and volatilization, generating nanopores of appropriate sizes. This avoids the structural collapse of the material caused by rapid heating and ensures better structural stability, thereby improving the material's cycle performance, rate performance, and capacity retention at low temperatures.
[0070] Soft-pack battery performance test: Using the negative electrode active materials of Examples 1-4 and Comparative Examples 1-2 as negative electrode active substances, and the positive electrode active material ternary material (LiNi) 1 / 3 Co 1 / 3 Mn 1 / 3 O2), electrolyte, and separator were assembled into a 5Ah pouch cell. The separator was Celegard 2400, and the electrolyte was a LiPF6 solution (a 1:1 volume ratio mixture of EC and DEC, with a LiPF6 concentration of 1.1 mol / L). The fabricated pouch cell was subjected to HPPC (Hybrid Pulse Power Characterization) rate performance testing, and the test results are detailed in Table 3.
[0071] HPPC Ratio Performance: The device was charged with a 3C pulse and discharged with a 4C pulse, and its charging DC internal resistance (DCR) was tested under different states of charge (SOC) conditions (10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%).
[0072] Table 3 Performance characterization of the pouch cells corresponding to Examples 1-4 and Comparative Examples 1-2
[0073] As shown in Table 3, the DCR of Examples 1-4 is significantly lower than that of Comparative Examples 1-2. This is because the materials in the examples have a high diffusion coefficient and a low OI value, which is beneficial to the transport of lithium ions during charging and discharging, thereby reducing the DCR and improving the rate performance.
[0074] The above are merely preferred embodiments of the present invention and do not limit the patent scope of the present invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the patent protection scope of the present invention.
Claims
1. A negative electrode active material, characterized in that, The negative electrode active material includes a core material and a shell material that at least partially covers the core material: The core material includes porous graphite and nitrogen, lithium, carbon and oxygen elements doped into the pores of the porous graphite. The shell material includes lithium phosphate; The preparation method of the negative electrode active material includes the following steps: S1. Porous graphite, inorganic lithium salt compound, conductive agent and nitrogen-containing alkaline organic solvent are mixed and chemically deposited. During the chemical deposition process, lithium ions in the inorganic lithium salt compound and hydroxide ions in the nitrogen-containing alkaline organic solvent combine to form lithium hydroxide, which is deposited in the pores of the porous graphite to obtain the first precursor material. S2. The first precursor material is carbonized so that the deposited lithium hydroxide decomposes into lithium oxide and water vapor at the carbonization temperature. The water vapor volatilization leaves a microporous structure, resulting in porous lithium oxide and the second precursor material. S3. An organic solvent containing lithium phosphate is used to form a lithium phosphate deposition layer on the surface of the second precursor material by atomization deposition, followed by vacuum drying to obtain the negative electrode active material; In step S1, the inorganic lithium salt compound includes at least one of LiTi2(PO4)3, LiGe2(PO4)3, and LiZr2(PO4)3; the nitrogen-containing alkaline organic solvent includes at least one of dimethylacetamide, dimethylformamide, and phenylacetamide; the mass ratio of the porous graphite, the inorganic lithium salt compound, the conductive agent, and the alkaline organic solvent is 100:5-10:1-5:500-1000; the temperature of the chemical deposition treatment is 25-80℃; and the time of the chemical deposition treatment is 1-6 hours. In step S2, the carbonization temperature is 800-1200℃; the carbonization time is 1-6 hours.
2. The negative electrode active material as described in claim 1, characterized in that, The porous graphite has an average pore size of 8-12 μm; and / or, The thickness of the shell material is 0.5μm-2μm; and / or, The mass ratio of the porous graphite, nitrogen, lithium, carbon, oxygen, and lithium phosphate is 84-95.5:0.5-2:0.5-2:2-5:0.5-2:1-5.
3. A method for preparing a negative electrode active material as described in any one of claims 1 to 2, characterized in that, The preparation method of the negative electrode active material includes the following steps: S1. Porous graphite, inorganic lithium salt compound, conductive agent and nitrogen-containing alkaline organic solvent are mixed and chemically deposited to obtain the first precursor material. S2. The first precursor material is carbonized to obtain the second precursor material; S3. An organic solvent containing lithium phosphate is used to form a lithium phosphate deposition layer on the surface of the second precursor material by atomization deposition, followed by vacuum drying to obtain the negative electrode active material.
4. The method for preparing the negative electrode active material as described in claim 3, characterized in that, In step S1, the porous graphite is obtained through the following steps: S01. The coke raw material, metal, metal oxide and binder are mixed and pressed into blocks to obtain a mixture; the boiling point of the metal is less than the boiling point of the metal oxide. S02. Under an inert atmosphere, the mixture is graphitized to obtain the porous graphite.
5. The method for preparing the negative electrode active material as described in claim 4, characterized in that, In step S01, the mass ratio of the coke raw material, the metal, the metal oxide, and the binder is 100:1-5:1-5:10-30; and / or, In step S01, the coking raw material includes at least one of petroleum coke, needle coke, and pitch coke; and / or, In step S01, the metal includes at least one of potassium, sodium, and zinc; and / or, In step S02, the metal oxide includes at least one of tin oxide, titanium dioxide, vanadium oxide, iron oxide, and manganese oxide; and / or, The binder includes at least one of petroleum asphalt, coal tar pitch, and styrene.
6. The method for preparing the negative electrode active material as described in claim 4, characterized in that, Step S02 includes: The mixture is subjected to a first heat treatment under an inert atmosphere to volatilize the metal, thereby obtaining a first intermediate. The first intermediate is subjected to a second heat treatment to volatilize the metal oxide, thereby obtaining a second intermediate. The second intermediate is graphitized to obtain the porous graphite.
7. The method for preparing the negative electrode active material as described in claim 6, characterized in that, The temperature of the first heat treatment is 700-900℃; and / or, The first heat treatment lasts for 2-6 hours; and / or, The temperature of the second heat treatment is 1100-1400℃; and / or, The second heat treatment lasts for 2-6 hours; and / or, The graphitization treatment is performed at a temperature of 2800-3200℃; and / or, The graphitization process takes 6-24 hours.
8. The method for preparing the negative electrode active material as described in claim 3, characterized in that, In step S1, the conductive agent includes at least one of graphene, carbon nanotubes, and super carbon black; and / or, In step S3, the concentration of lithium phosphate in the organic solvent containing lithium phosphate is 1-5 wt%; and / or, In step S3, the temperature of the atomization deposition method is 60-200℃; and / or, In step S3, the pressure of the atomization deposition method is 1-10 MPa; and / or, In step S3, the atomization deposition method takes 30-300 minutes; and / or, In step S3, the vacuum drying temperature is 80~90℃; and / or, In step S3, the vacuum drying time is 22-26 hours.
9. A negative electrode sheet, characterized in that, The negative electrode sheet comprises the negative electrode active material as described in any one of claims 1 to 2 or the negative electrode active material prepared by the preparation method of the negative electrode active material as described in any one of claims 3 to 8.
10. A lithium-ion battery, characterized in that, The lithium-ion battery includes the negative electrode as described in claim 9.
Citation Information
Patent Citations
Solid electrolyte doped amorphous carbon coated graphite composite material and preparation method thereof
CN118970003A
Composite material as well as preparation method and application thereof
CN119069681A
Graphite composite material and preparation method and application thereof
CN120545338A